Bioremediation model for atrazine contaminated agricultural soils using phytoremediation (using Phaseolus vulgaris L.) and a locally adapted microbial consortium. Issue 6 (3rd June 2017) - Madariaga-Navarrete, Alfredo; Rodríguez-Pastrana, Blanca Rosa; Villagómez-Ibarra, José Roberto; Acevedo-Sandoval, Otilio Arturo; Perry, Gregory; Islas-Pelcastre, Margarita
ABSTRACT: The objective of the present study was to examine a biological model under greenhouse conditions for the bioremediation of atrazine contaminated soils. The model consisted in a combination of phytoremediation (using Phaseolus vulgaris L.) and rhizopheric bio-augmentation using native Trichoderma sp., and Rhizobium sp. microorganisms that showed no inhibitory growth at 10, 000 mg L −1 of herbicide concentration. 33.3 mg of atrazine 50 g −1 of soil of initial concentration was used and an initial inoculation of 1 × 10 9 UFC mL −1 of Rhizobium sp. and 1 × 10 5 conidia mL −1 of Trichoderma sp. were set. Four treatments were arranged: Bean + Trichoderma sp. (B+T); Bean + Rhizobium sp. (BR); Bean + Rhizobium sp. + Trichoderma sp. (B+R+T) and Bean (B). 25.51 mg of atrazine 50 g −1 of soil (76.63%) was removed by the B+T treatment in 40 days ( a = 0.050, Tukey). This last indicate that the proposed biological model and methodology developed is useful for atrazine contaminated bioremediation agricultural soils, which can contribute to reduce the effects of agrochemical abuse.